(untitled) (Journal of the College of Basic Education, 2025)
The research aims to identify the impact of the SQ4R strategy on the development of silent reading skills among middle school students. To verify the goal, the researcher developed a null hypothesis: there is no statistically significant difference between the average scores of the experimental group studying with SQ4R and the control group studying traditionally. The sample included 60 female students randomly selected from Al-Amjad school in Baghdad. Both groups were equalized in age, parents’ education, Arabic grades, and prior reading skills. After a semester-long experiment and a 25-item post-test, results showed a significant difference favoring the experimental group.